2019
DOI: 10.1371/journal.pone.0213867
|View full text |Cite
|
Sign up to set email alerts
|

Corn gluten meal induces enteritis and decreases intestinal immunity and antioxidant capacity in turbot (Scophthalmus maximus) at high supplementation levels

Abstract: Corn gluten meal (CGM) is an important alternative protein source in aquafeed production. However, in turbot (Scophthalmus maximus), CGM could not be effectively utilized because of its low digestibility, the reason for which is still unclear. The purpose of the present study was to investigate and elucidate the cause for the poor utilization of CGM by turbot from the view of gut health. An 8-week feeding trial was conducted with turbot individuals (initial body weight 11.4 ± 0.2 g), which were fed with one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 72 publications
2
29
2
Order By: Relevance
“…Interestingly, no significantly differentially expressed transcripts involved in inflammation were found in the RNA-Seq results, which support the lack of histological abnormality in this study. This result contrasts with studies on California yellowtail, S. dorsalis [23], Atlantic salmon, S. salar [28,46] and turbot, Scophthalmus maximus [47]. The differences with our finding might be related to the longer trial duration in those studies (56 days to 96 days) or the varying response in different species.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, no significantly differentially expressed transcripts involved in inflammation were found in the RNA-Seq results, which support the lack of histological abnormality in this study. This result contrasts with studies on California yellowtail, S. dorsalis [23], Atlantic salmon, S. salar [28,46] and turbot, Scophthalmus maximus [47]. The differences with our finding might be related to the longer trial duration in those studies (56 days to 96 days) or the varying response in different species.…”
Section: Discussioncontrasting
confidence: 99%
“…Corn gluten meal (CGM) is a good source of protein having at least 63% protein and low fat which has been used for its beneficial effects as a source of protein in the diet of Pacific white shrimp . CGM is an important protein part obtained from the wet milling process for the isolation of the starch, germ, protein and fiber components of corn . However, as a plant protein, CGM also contains some ANFs and limiting amino acids .…”
Section: Introductionmentioning
confidence: 99%
“…Proximal portion of fish intestine (PI) is credited with higher nutrients digestibility and absorption and overall digestive capacity (Krogdahl et al, 2003). It is well documented that the anti-nutritional factors present in soybean products and/or CG can cause moderate or severe enteritis in European seabass (Cuoto et al, 2015, Rimoldi et al, 2016, Bai et al, 2019. In the present study, although no overt inflammation was observed, fish fed the lowest FM level (20%) presented some alterations in their PI morphological structure when compared with fish fed the CTRL or other PX diets (Fig 2A-C).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still apparent and unidentified biologically active compounds in plant products that inhibit the complete replacement of FM in carnivorous fish feeds (Gatlin et al, 2007;Glencross, 2016). Although these plant protein ingredients are among the most commonly used for FM replacement in fish feeds, their use in salmonid, European seabass, gilthead seabream and turbot feeds is limited due to the development of induced inflammation in the distal intestine (enteritis) of these fish (Kokou et al, 2015;Rimoldi et al, 2016;Bai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation